Fingolimod Potentiates the Antifungal Activity of Amphotericin B - Wei, Lu-Qi; Tan, Jing-Cong; Wang, Yue; Mei, Yi-Kun; Xue, Jia-Yu; Tian, Lei; Song, Ke-Yu; Han, Lu; Cui, Ying-Chao; Peng, Yi-Bing; Li, Jing-Quan; Liu, Ning-Ning; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Candida albicans (C. albicans) is an opportunistic human fungal pathogen that can cause severe infection in clinic. Its incidence and mortality rate has been increasing rapidly. Amphotericin B (AMB), the clinical golden standard antifungal agent, has severe side effects that limit its clinical application. Thus, lowering the concentration and increasing the efficacy of AMB in a combinatorial antifungal therapy have been pursued by both industry and academia. Here we identify that fingolimod (FTY720), an immunomodulatory drug used for oral treatment of relapsing-remitting multiple sclerosis, can potentiate the efficacy of AMB against C. albicans growth synergistically. Furthermore, we observe an antifungal efficacy of FTY720 in combination with AMB against diverse fungal pathogens. Intriguingly, cells treated with both drugs are hypersensitive to endothelial endocytosis and macrophage killing. This is later found to be due to the hyperaccumulation of reactive oxygen species and the corresponding increase in activities of superoxide dismutase and catalase in the cells that received combinatorial treatment. Therefore, the combination of AMB and FTY720 provides a promising antifungal strategy.